Optimization and Validation of HPLC-DAD Method for the Quantification of Curcuminoids in Turmeric (Curcuma Longa L.) - Sap, Ayse; Yaman, Mehmet (Univ Sindh, Natl Centre Excellence Analytical Chemistry, 2022)
Curcumin and its derivatives named curcuminoids are naturally occurring polyphenolic compounds extensively marketed as a nutraceutical. The wide therapeutic potential of curcumin is highly explored by the authors. Therefore, pharma industries made many clinical inventions to bring it to the market as a drug. In this study, a simple, rapid, and sensitive High Performance Liquid chromatographic (HPLC) method for simultaneous determinations of curcumin, desmethoxycurcumin (DMC), and bis-desmethoxycurcumin (BDMC) was optimized and validated. Separation of curcumin, DMC, and BDMC was performed using the C18 column. Six factors, including the solvent type, ratio of mobile phase, flow rate of mobile phase, column temperature, injection volume, and wavelength, were investigated. The LOD and LOQ were observed to be 0.001 and 0.003 mg/L, R-2 value < 0,99, respectively. RSD (%) is 0.974 for inter-day, and 1,312 for intra-day. Taking into consideration the retention time, peak area, resolution, and tailing factor, the optimum conditions were preferred: methanol as solvent, THF/Citric Acid (40/60) as mobile phase, flow rate of mobile phase at 0.5 mL/min, temperature of column at 30 degrees C, injection volume at 20 mu L and wavelength at 425 nm. The method is further used to determine ppm levels of curcumin derivatives, and recovery was found to be 90%. The proposed analytical method can be used for the quantification of curcumin in medicinal plants.
Keywords: Curcumin; Method validation; HPLC; Optimization in analysis